“It’s because of what we did that I’m going to university”:: A qualitative exploration of the experience of growing through a school’s therapeutic programme - Noor, Lydia (European Journal for Qualitative Research in Psychotherapy, 2011)
This study aimed to ‘give voice’ to the lived experience and perceptions of seven students (aged 15 to 17) who have used a therapeutic service in school. Group or individual interviews were employed, tran- scribed and then analysed using a phenomenologically-orientated relational research methodology. The students all expressed valuing a confidential one-to-one space where they could express and explore their worries and uncertainties. They benefitted from feeling understood and having their perspective validated as ‘normal’. The opportunity to express feelings that distracted them from learning at school opened up new skills of reflection, negotiation and being able to reach out for support. Through their therapeutic experiences they learned to invest in their own success and resist potentially destructive peer pressure. A short discussion raises wider issues around the provision of therapy in secondary school settings.